Estimasi Hasil Panen Ayam Pedaging Menggunakan Algoritma Regresi Linear Berganda - Ahyani Junia Karlina; Muhammad Irsyad; Fitri Insani; Jasril; Eka Pandu Cynthia (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Data mining is the process of collecting and managing information that aims to extract important data from data. Currently data mining is used by companies to manage data but there are still many companies engaged in the livestock sector that have not used data mining to manage data. One of these companies is PT.PX which is a broiler company located in Riau, precisely in Sungai Pagar. The ever-increasing need for broiler chickens makes it difficult for chicken breeders to produce chicken according to market demand in each period. Unpredictable demand for broiler chickens makes breeders confused to determine how many chicks to produce. PT.PX still manages data using Microsoft Excel so the process is still very long and it is not certain to get accurate results. PT.PX also does not have a system for predicting broiler yields to find out how many chicken populations there will be in the next period. The existence of this data mining can help breeders to find out the number of populations to be produced for the next period. In predicting broiler yields, estimation methods can be used using multiple linear regression algorithms. Multiple linear regression was used to determine the relationship between feed, weight and age of chickens and chicken population. The information used in this research is information on harvested chickens obtained from 2019 to 2022. The results of multiple linear regression calculations at PT.PX obtained broiler yields of 12,217 populations